Peutz-Jeghers syndrome revealed by CT finding of acute small bowel intussusception: A case report - Paola Milillo, MD, PhD; Gianluca Prencipe, MD; Stefano Piscone, MD; Sara Saccone, MD; Luca Cappucci, MD; Maria Grazia Scarale, MD; Roberta Vinci, MD; Luca Macarini, MD; Luca Pio Stoppino, MD, PhD (Radiology Case Reports)
Peutz-Jeghers syndrome (PJS) is a rare genetic disorder characterized by multiple gastrointestinal hamartomatous polyps and distinctive mucocutaneous pigmentations. Intussusception is a significant complication associated with Peutz-Jeghers syndrome and it can lead to potential bowel obstruction and ischemia. We present a case report in which PJS was first suspected by a radiologist after performing abdomen Computed Tomography (CT) at the emergency department. We will discuss the clinical presentation, radiological findings and surgical management in a case of acute small bowel intussusception.